(untitled) (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2026)
Background and Aim. Social media plays a significant role in shaping body perception; however, its impact among individuals with physical disabilities remains underexplored. This study aimed to examine the relationships between active and passive social media use and body esteem, body mass index (BMI), and physical activity in adults with physical disabilities. Methods. A cross-sectional survey design was employed. Data were collected from 271 participants between the 1st of April and the 7th of April 2025, through organisations representing individuals with physical disabilities. The mean age was 43.32 years, 73.4% were women, and mean BMI was 25.5 kg/m². Body esteem was assessed using the Body Esteem Scale for Adolescents and Adults (BESAA), evaluating appearance, weight, and attribution domains. Data were analysed using descriptive statistics, Pearson correlations, independent-samples t-tests, and hierarchical multiple regression analyses. Results. Younger participants reported higher levels of active (r = −.482, p < .001) and passive (r = −.446, p < .001) social media use. Women demonstrated significantly greater active and passive use than men (p < .001), while no differences were observed across educational levels. Regression analyses showed that models explained 29.0% of variance in appearance-, 44.5% in weight-, and 31.1% in attribution-related body esteem (all p < .001). Active social media use was positively associated with appearance- and attribution-related body esteem. Physical activity was a positive predictor across all body esteem dimensions (p ≤ .002), whereas higher BMI was negatively associated with weight-related body esteem (β = −.283, p < .001). Conclusions. Social media use patterns may differentially influence body esteem in individuals with physical disabilities. Active engagement appears beneficial in selected domains, while physical activity represents a key protective factor. These findings may inform interventions aimed at improving body image and overall wellbeing in this population. Keywords: Physical disability; social media; body image